2014
DOI: 10.1002/zoo.21131
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-year proximity relationships in a captive group of western lowland gorillas (Gorilla gorilla gorilla) at the San Diego Wild Animal Park, California, USA

Abstract: Proximity data were collected in a captive breeding group of gorillas (Gorilla gorilla gorilla) at the San Diego Wild Animal Park (currently called the San Diego Zoo Safari Park) twice a year (spring and fall periods) for over 12 years, by using a convenient method in which individuals less than 5 m from each animal in the group were recorded by scan sampling, approximately once per hour. Immature females from infancy to young adulthood maintained relatively frequent proximity to both their mothers and the sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(57 reference statements)
0
4
1
Order By: Relevance
“…In this study, contrary to what is reported in the literature on wild and captive lowland gorillas (Fischer 1983;Stoinski et al 2003;Stokes 2004;Nakamichi et al 2014;Klailova and Lee 2014), adult females spent more time in spatial proximity to the silverback than to other females. In this view, the probability of social interaction (including play) between the silverback and adult females was enhanced.…”
Section: Presence Of Adult-adult Playcontrasting
confidence: 99%
“…In this study, contrary to what is reported in the literature on wild and captive lowland gorillas (Fischer 1983;Stoinski et al 2003;Stokes 2004;Nakamichi et al 2014;Klailova and Lee 2014), adult females spent more time in spatial proximity to the silverback than to other females. In this view, the probability of social interaction (including play) between the silverback and adult females was enhanced.…”
Section: Presence Of Adult-adult Playcontrasting
confidence: 99%
“…The low association indices amongst individuals are similar to those reported between male-female mountain gorilla dyads within 2m in nature [ 4 ] suggesting the GRACE gorillas associate with one another similarly to mountain gorillas, their closest relatives. Association patterns of gorillas in zoos vary widely by study making comparisons to our findings challenging [ 49 , 70 72 ]. This may be reflective of the diversity of group-types, living spaces and management procedures within zoos, and possibly because the reporting of association patterns in zoos are often focused on a specific applied perspective, rather than a broad description of gorilla life in general.…”
Section: Discussionmentioning
confidence: 99%
“…As familiarity is the presumed underlying proximate mechanism driving kin biased behavior [ 74 ], it could be that the GRACE females who have lived together for many years since they were young have developed a familiarity with each other that is similar to what is observed in nature. Data from zoos, where females often live in groups for longer periods of time than they would in nature, similarly suggest that stronger association patterns amongst adult females occur compared to what is observed in nature [ 29 , 49 ]. Thus, these strong female-female relationships may be an artifact of living in human care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations